Small Mammals from Samunsam Wildlife Sanctuary, Sarawak, Malaysian Borneo - Faisal Ali, Anwarali Khan; Nurul Farah Diyana, A. Tahir; Sultana Parvin, Binti Habeebur Rahman; Julius Willian, Dee; Muhd Amsyari, Morni; Qhairil Shyamri, Rosli; Roberta Chaya, Tawie Tingga; Mohd Ridwan, Abd Rahman; Isham, Azhar (Universiti Malaysia Sarawak (UNIMAS), 2017)
Small mammal survey was conducted at Samunsam Wildlife Sanctuary (WS) from 20th until 25th October 2014. This survey aimed to assess the diversity of small mammals particularly from the order Chiroptera, Insectivora, Rodentia and Scadentia. These orders were targeted primarily to gain better understanding on the ecology and distribution of these understudied taxa in Borneo. Our survey recorded a total of 30 species of small mammals from six trapping nights. Order Chiroptera was recorded with the highest number of species (seven families; 22 species), followed by order Rodentia (two families; six species) and order Scandentia (two species). None was recorded from the order Insectivora. The most abundant species were Rhinolophus trifoliatus (n=6) for Chiroptera, Maxomys whiteheadi (n=7) for Rodentia and Tupaia tana (n=5) for Scandentia. Data presented here is the first comprehensive information on Samunsam’s small mammals. This data can be used to gain better insights on the population trends at regional and local scale, as well as in improving the management plans of Samunsam WS. Although species diversity in Samunsam WS is comparable to other sites in western Sarawak, result presented here need to be treated with caution as this is the first comprehensive study that only cover area close to park headquarters.